Energy Loss Analysis For Distribution Pipe Network System In Sabak Auh District - Riyan Irawan; Siswanto Siswanto; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Having cleaning water service is a public right. To date, however, clean water is a scarce for people of Sabak Auk District. Therefore, in order to meet the public demand, the Siak District administrator is required to increase the drinking water supplying system for district capital (SPAM IKK) in Sabak Auh. The primary water resource used by Regional Water Utility Company (PDAM) in Sabak Auh District comes from raw water originated from Parit Belading/Sudetan Siak Kecil which is transferred to water treatment plant in Sabak Auh District. Following processing, the water is transported through the transmission pipeline to the reservoir where the water is subsequently distributed to the consumers by means of distribution pipeline. The method used in this study is by performing Epanet 2.0, a computerized simulation model, approach by way of predicting the amount of water demand for the next few years till 2035. By using the consumer water demand data and the area map of Sabak Auh District, the clean water distribution service area is subsequently created. Total distribution pipe length is 20,320.84 m by means one pump of 10 l/s in capacity with 50 m head height. This clean water distribution system simulation of Sabak Auh District area is expected be to guidance in distribution pipeline plan of Regional Water Utility Company in Sabak Auh in the future. Keywords: Epanet, distribution system, clean water, Regional Water Utility Company (PDAM).